Analyzing Physics Learning to Determine the Character and Self-Efficacy of High School Students - Hadijah, Siti; Sarwi, Sarwi; Masturi, Masturi (Physics Communication, 2022)
Research has been carried out to analyze learning based on the character and friendly attitude of students. The purpose of this study is how the character and self-interest of students in learning physics in a learning model. The research design used was quantitative research with survey research. The research sample was public high school and private high school in Semarang. The instrument used was a questionnaire using a google form. The results of this study were the lack of student character in learning, one of which was the student's curiosity in learning with a character proportion of 48%. Then, the proportion of students' self-confidence or self-confidence is still classified as low category. Students who lack confidence in their achievements and in doing assignments at school can affect learning models that are less precise and effective.